2021
DOI: 10.1002/cphc.202100250
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Behaviors of S‐, O‐, and N‐containing Aliphatic Molecules with a Propyl Moiety on Ge(100) Surface

Abstract: The reaction pathways of 1-propanethiol, 1-propanol, and propylamine molecules, containing a propyl moiety, on a Ge(100) surface were investigated using high-resolution photoemission spectroscopy (HRPES) experiments and density functional theory (DFT) calculations. Upon analysis of the HRPES data, the adsorption of 1-propanethiol and 1-propanol was found to occur through a dissociation reaction, whereas that of propylamine took place via N dative bonding at room temper-ature. On the basis of our DFT results, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…All of the S 2p spectra contain two distinct peaks at 162.1 and 164.3 eV (marked as S 1 and S 2 ), indicating the presence of two types of sulfur species of different chemical states. In earlier studies, S 2p 3/2 peaks observed in the range of 162.0–162.6 eV on the Ge(100) surface were ascribed to a neutral sulfur atom in the S–H dissociated species, whereas those observed in the range of 164.0–164.2 eV were attributed to a positively charged sulfur atom in an S dative-bonded structure. ,, Accordingly, we assigned the peak at 164.3 eV in the S 2p core-level spectra to the molecularly adsorbed C 4 H 8 S–Ge structure, which has a positively charged sulfur atom, resulting from S dative bonding. In the case of previously reported adsorption of tetrahydrofuran on the Ge(100) surface, the O 1s peak related to an adsorption structure with an interdimer row Ge–(CH 2 ) 4 –O–Ge configuration, formed through a ring-opening reaction, appeared at the spectral position corresponding to the binding energy of a neutral oxygen atom .…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…All of the S 2p spectra contain two distinct peaks at 162.1 and 164.3 eV (marked as S 1 and S 2 ), indicating the presence of two types of sulfur species of different chemical states. In earlier studies, S 2p 3/2 peaks observed in the range of 162.0–162.6 eV on the Ge(100) surface were ascribed to a neutral sulfur atom in the S–H dissociated species, whereas those observed in the range of 164.0–164.2 eV were attributed to a positively charged sulfur atom in an S dative-bonded structure. ,, Accordingly, we assigned the peak at 164.3 eV in the S 2p core-level spectra to the molecularly adsorbed C 4 H 8 S–Ge structure, which has a positively charged sulfur atom, resulting from S dative bonding. In the case of previously reported adsorption of tetrahydrofuran on the Ge(100) surface, the O 1s peak related to an adsorption structure with an interdimer row Ge–(CH 2 ) 4 –O–Ge configuration, formed through a ring-opening reaction, appeared at the spectral position corresponding to the binding energy of a neutral oxygen atom .…”
Section: Resultsmentioning
confidence: 83%
“…According to previous studies, for the Ge−S−CH 2 −CH 3 and Ge−S−CH 2 −CH 2 −CH 3 configurations formed through the dissociation of ethyl disulfide and 1-propanethiol on a Ge(100) surface, the C 1s peak appeared as a single component at 284.4 and 284.6 eV, respectively. 11,14 The fact that the signals of all the carbon atoms in ethyl and propyl groups appeared at the same binding energy in earlier studies indicates that the binding energies of the first and second nearest carbon atoms next to the carbon atom directly bonded to the neutral sulfur atom should also be in the range of 284.4−284.6 eV. Thus, we infer that the C 1s peaks corresponding to C a and C β in Figure 2 are overlapped at 284.6 eV in the C 1s spectra.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since a dimer on the reconstructed (100) surface of a Group 14 semiconductor simultaneously exhibits π-bonding and zwitterion characteristics, it can react with organic molecules via cycloaddition and Lewis acid–base reactions 9 13 . Because a molecule containing two C=C bonds, such as butadiene, can act as a conjugated diene, a five-membered aromatic molecule containing a heteroatom and two C=C bonds in the ring system can also serve as a conjugated diene and initiate a [4 + 2] cycloaddition reaction with the surface dimer of Ge(100) or Si(100) while functioning as a dienophile 14 .…”
Section: Introductionmentioning
confidence: 99%